Polymeric and inorganic nanoscopical antimicrobial fillers in dentistry. (1st January 2020) - Makvandi, Pooyan; Gu, Jun Ting; Zare, Ehsan Nazarzadeh; Ashtari, Behnaz; Moeini, Arash; Tay, Franklin R.; Niu, Li-na
Abstract: Failure of dental treatments is mainly due to the biofilm accumulated on the dental materials. Many investigations have been conducted on the advancements of antimicrobial dental materials. Polymeric and inorganic nanoscopical agents are capable of inhibiting microorganism proliferation. Applying them as fillers in dental materials can achieve enhanced microbicidal ability. The present review provides a broad overview on the state-of-the-art research in the field of antimicrobial fillers which have been adopted for incorporation into dental materials over the last 5 years. The antibacterial agents and applications are described, with the aim of providing information for future investigations. Statement of significance: Microbial infection is the primary cause of dental treatment failure. The present review provides an overview on the state-of-art in the field of antimicrobial nanoscopical or polymeric fillers that have been applied in dental materials. Trends in the biotechnological development of these antimicrobial fillers over the last 5 years are reviewed to provide a backdrop for further advancement in this field of research. Graphical abstract: Image, graphical abstract